Transgelins, cytoskeletal proteins implicated in different aspects of cancer development - Dvorakova, Monika; Nenutil, Rudolf; Bouchal, Pavel (Expert review of proteomics, 2014)
Transgelin is an abundant protein of smooth muscle cells, where its role has been primarily studied. As a protein affecting dynamics of the actin cytoskeleton via stabilization of actin filaments, transgelin is both directly and indirectly involved in many cancer-related processes such as migration, proliferation, differentiation or apoptosis. Transgelin was previously reviewed as a tumor suppressor; however, recent data based on a number of proteomics studies indicate its pro-tumorigenic role, for example, in colorectal or hepatocellular cancer. We summarize these contradictory observations in both clinical and functional proteomics projects and analyze the role of transgelin in tumors in detail. Generally, the expression and biological role of transgelin seem to differ among various types of tumor cells and stroma, and possibly change during tumor progression. We also overview the recent data on transgelin-2, a sequence homolog of transgelin, whose role in the tumor development might be contradictory to the role of transgelin.
Keywords: Neoplasm Invasiveness; Tumor Microenvironment; Cell Movement; nádorové mikroprostředí; apoptóza; Actins; proteomika; stárnutí buněk; Microfilament Proteins; svalové proteiny; aktiny; Carcinogenesis; Cellular Senescence; epitelo-mezenchymální tranzice; Epithelial-Mesenchymal Transition; Biomarkers, Tumor; Neoplasms; Muscle, Smooth; Proteomics; nádorové biomarkery; Cytoskeletal Proteins; Humans; cytoskeletální proteiny; pohyb buněk; nádory; mikrofilamentové proteiny; invazivní růst nádoru; Muscle Proteins; Neoplastic Stem Cells; karcinogeneze; nádorové kmenové buňky; hladké svalstvo; lidé; Apoptosis